Effektivitas Konseling Teknik Assertive Training dalam Mereduksi Perilaku Konformitas pada Kelompok Teman Sebaya - Majdi, M. Zuhdi Zainul; Himsonadi, Himsonadi (Universitas Muria Kudus, 2024)
Adolescence is a stage between childhood and maturity. The process of self-adjustment is one type of adaptation. People attempt to be liked and accepted in order to build strong connections, therefore they often change their behavior, one of which is by complying. The goal of the study was to determine how effectively aggressive training strategies reduced peer group conformity. A one-group pretest-posttest design was used in this research. Seven people were the study's subjects. Purposive sampling is the method of sample elimination used. An assessment of conformity behavior was used to collect data. T-test statistics were employed for data analysis. The findings indicated that aggressive teaching strategies had a positive impact on lowering peer group conformity